The Santorini-Amorgos Shear Zone: Evidence for Dextral Transtension in the South Aegean Back-Arc Region, Greece - Konstantina Tsampouraki-Kraounaki; Dimitris Sakellariou; Grigoris Rousakis; Ioannis Morfis; Ioannis Panagiotopoulos; Isidoros Livanos; Kyriaki Manta; Fratzeska Paraschos; George Papatheodorou (Geosciences, 2021)
Bathymetric and seismic data provide insights into the geomorphological configuration, seismic stratigraphy, structure, and evolution of the area between Santorini, Amorgos, Astypalea, and Anafi islands. Santorini-Amorgos Shear Zone (SASZ) is a NE-SW striking feature that includes seven basins, two shallow ridges, and hosts the volcanic centers of Santorini and Kolumbo. The SASZ initiated in the Early Pliocene as a single, W-E oriented basin. A major reorganization of the geodynamic regime led to (i) reorientation of the older faults and initiation of NE-SW striking ones, (ii) disruption of the single basin and localized subsidence and uplift, (iii) creation of four basins out of the former single one (Anafi, Amorgos South, Amorgos North, and Kinairos basins), (iv) rifting of the northern and southern margins and creation of Anydros, Astypalea North, and Astypalea South basins, and (v) uplift of the ridges. Dextral shearing and oblique rifting are accommodated by NE-SW striking, dextral oblique to strike-slip faults and by roughly W-E striking, normal, transfer faults. It is suggested here that enhanced shearing in NE-SW direction and oblique rifting may be the dominant deformation mechanism in the South Aegean since Early Quaternary associated with the interaction of North Anatolian Fault with the slab roll-back.